2013
DOI: 10.2140/gt.2013.17.93
|View full text |Cite
|
Sign up to set email alerts
|

Width is not additive

Abstract: We develop the construction suggested by Scharlemann and Thompson in [14] to obtain an infinite family of pairs of knots Kα and K α so that w(Kα#K α ) = max{w(Kα), w(K α )}. This is the first known example of a pair of knots such that w(K#K ) < w(K) + w(K ) − 2 and it establishes that the lower bound w(K#K ) ≥ max{w(K), w(K )} obtained in [12] is best possible. Furthermore, the knots Kα provide an example of knots where the number of critical points for the knot in thin position is greater than the number of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…This result is generalized in [5], where it was shown that any other bridge surface of such a knot must also have high genus or a high number of marked points. Several other recent constructions of interesting examples rely on such knots -in [2] Blair and Tomova construct knots for which width is not additive, and in [4] Johnson and Tomova construct examples of knots with two different bridge surfaces that require a high number of stabilizations and perturbations to become isotopic.…”
Section: Introductionmentioning
confidence: 99%
“…This result is generalized in [5], where it was shown that any other bridge surface of such a knot must also have high genus or a high number of marked points. Several other recent constructions of interesting examples rely on such knots -in [2] Blair and Tomova construct knots for which width is not additive, and in [4] Johnson and Tomova construct examples of knots with two different bridge surfaces that require a high number of stabilizations and perturbations to become isotopic.…”
Section: Introductionmentioning
confidence: 99%
“…(2) There exist two knots K and K ′ in Figure 4 Note that a knot K in Figure 4 is not in a thin position, thus we have γ ∈ M CP (K)\T P (K). Moreover, we remark that there exists a knot K = K α in [8] such that T P (K) ∩ M CP (K) = ∅.…”
Section: Several Versions Of Thin Positionmentioning
confidence: 99%
“…Example 3.2. For a knot K ∈ K given in Theorem 1.3, by [8], there exists γ ∈ K in Figure 3 such that γ ∈ T P (K)\M CP (K) and γ is not in OT P (K) since there exists an embedding of K with two thick levels of width 10 and two thick levels of width 8. Since it is shown in [8] that every γ ∈ T P (K) has exactly three thick levels, each of width 10, we have pro(K) = 10 3 1 2 × 11 = 0.1515 .…”
Section: Several Versions Of Thin Positionmentioning
confidence: 99%
“…In this study I focused on constructing and making practical use of an axiomatic basis for MHA from biological considerations alone. Nonetheless, it will be interesting to study whether there are applicable theoretical treatments of low-dimensional topological objects, such as from mathematical knot theory [e.g., Blair and Tomova (2013)] or from models of quantum gravity in physics [e.g., Carlip (2017)]. If so there may exist additional mathematical tools that can be adapted for the alignment of two dimensional biological sequence homology.…”
Section: Mha Widths Are Not Additivementioning
confidence: 99%